Perlindungan Hukum Anak Korban Eksploitasi Seksual Komersial Dalam Perspektif Convention on The Right Of The Child (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
In an effort to create fulfillment of rights and special protection for children, the Convention On The Right Of The Child aims to encourage international cooperation among countries that have ratified the Convention On The Right Of The Child to improve a decent life for children, especially in developing countries. -developing countries and provide full protection for children to avoid crimes that can endanger their lives such as commercial sexual exploitation. The type of research used in this study is normative legal research, which is a type of legal research to find a rule of law, legal principles, or legal doctrines to answer the legal issues at hand. This research will describe to what extent the written positive laws are synchronous or in harmony with each other. Article 34 of the convention on the right of the child is the basis of international law regarding commercial sexual exploitation, in which it emphasizes that participating countries must strive to be able to provide protection to children, so as to avoid all forms of sexual exploitation, Indonesia as a country that has ratified the convention on the right of the child has attempted to develop national legal instruments to provide protection for children to avoid the dangers of sexual violence, but legal instruments have not been able to accommodate the dangers of commercial sexual exploitation of children, because there is still a lack of definition and cannot explain forms of commercial sexual exploitation in instruments existing laws.